Genetic basis for a rare floral mutant in an Andean species of Solanaceae1. Issue 2 (1st February 2015) - Coburn, Rachel A.; Griffin, Randi H.; Smith, Stacey D.
Abstract : Premise of the study: White forms of typically pigmented flowers are one of the most common polymorphisms in flowering plants. Although the range of genetic changes that give rise to white phenotypes is well known from model systems, few studies have identified causative mutations in natural populations. Methods: Here we combine genetic studies, in vitro enzyme assays, and biochemical analyses to identify the mechanism underlying the loss of anthocyanin pigment production in the naturally occurring white‐flowered morph of Iochroma calycinum (Solanaceae). Key results: Comparison of anthocyanin gene sequences revealed a putative loss‐of‐function mutation, an 11 amino‐acid deletion in dihydroflavonol 4‐reductase (DFR), in the white morph. Functional assays of Dfr alleles from blue and white morphs demonstrated that this deletion results in a loss of enzymatic activity, indicating that the deletion could be solely responsible for the lack of pigment production. Consistent with this hypothesis, quantitative PCR showed no significant differences in expression of anthocyanin genes between the morphs. Also, thin layer chromatography confirmed that the white morph continues to accumulate compounds upstream of the DFR enzyme. Conclusions: Collectively, these experiments indicate that the structural mutation at Dfr underlies the rare white flower morph of I. calycinum . This study is one of only a few examples where a flower color polymorphism is due to a loss‐of‐function mutation in the coding region of an anthocyanin enzyme. The rarity of such mutations in nature suggests that negative consequences prevent fixation across populations.